Retinoid antagonism of NF-IL6: insight into the mechanism of antiproliferative effects of retinoids in Kaposi's sarcoma. - Nagpal, S (1997)
All-trans-retinoic acid (RA) is active in the treatment of Kaposi's sarcoma (KS), and retinoids inhibit KS cell growth in vitro. To understand the mechanism of retinoid action in KS, we studied the expression of autocrine growth factors of KS cells after RA treatment. We demonstrate that RA and its synthetic analogs inhibit the proliferation of KS cells by inhibiting the mRNA and protein levels of interleukin-6 (IL-6), an autocrine growth factor for KS cells. We further demonstrate that nuclear retinoid receptors (RA receptors [RARs] and retinoid X receptors [RXRs]) inhibit IL-6 promoter action by antagonizing the enhancer action of NF-IL6, a basic domain leucine zipper transcription factor belonging to the family of CAAT enhancer binding proteins. Furthermore, RARs and RXRs do not bind in vitro to an NF-IL6 binding site. However, the secondary folded structure of the DNA binding domain of RAR and RXR is obligatory for inhibiting NF-IL6 activity. Thus, NF-IL6 is a potential therapeutic target for the treatment of KS. Finally, using receptor-selective synthetic retinoids, we demonstrate that NF-IL6 antagonism and transactivation are separable functions of RAR alpha, thus indicating that synthetic retinoids with properties of NF-IL6 antagonism but lacking transactivation capabilities can be synthesized. Such retinoids might increase therapeutic potential in KS.